A method for recycling secondary aluminum ash and its application

By washing, calcining and crystallizing the secondary aluminum ash, modified alumina is obtained, which solves the problems of low extraction rate and poor compatibility in the existing process, and achieves efficient recycling and performance improvement.

CN117623349BActive Publication Date: 2025-04-22FOSHAN LIANGHUI ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202311496290.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-10
Publication Date
2025-04-22
Estimated Expiration
2043-11-10

AI Technical Summary

Technical Problem

The existing secondary aluminum ash recycling process has problems such as complex process, low extraction rate, high cost, poor compatibility and insufficient dispersion in the application of recycling products in the chemical field, which affects the quality and performance of the product.

Method used

By washing the secondary aluminum ash with water, calcining with ammonium sulfate, water immersing and cooling the crystals, alumina is obtained, and alumina is obtained by calcining at high temperature. The alumina is then hydroxylated and blended with carboxymethylcellulose, and the modified alumina is obtained by ultrasonic heating.

Benefits of technology

The dispersion, compatibility and stability of alumina in composite materials are improved, the product performance is significantly improved, and the efficient recycling and utilization of secondary aluminum ash is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a method for recycling secondary aluminum ash and its application, wherein the method comprises the following steps: S1, pre-treating the secondary aluminum ash by heating and washing, then mixing it with ammonium sulfate, roasting and water-immersing it to obtain a leachate, then cooling and crystallizing the leachate, separating the solid, and calcining it to obtain aluminum oxide; S2, hydroxylating the aluminum oxide to obtain hydroxylated aluminum oxide; S3, blending the hydroxylated aluminum oxide with carboxymethyl cellulose, and reacting it by ultrasonic heating to obtain modified aluminum oxide. The present invention improves the dispersibility, compatibility and stability of the modified aluminum oxide in composite materials while efficiently recycling the secondary aluminum ash, and can significantly improve product performance by using it as a filler in the fields of polymer materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum ash recycling, and specifically relates to a secondary aluminum ash recycling method and application thereof. Background Art

[0002] Aluminum ash is a waste produced during the production and processing of aluminum metal. Aluminum ash is divided into primary aluminum ash and secondary aluminum ash according to its source. Primary aluminum ash is aluminum slag directly obtained from the smelting furnace, which still has a high aluminum content, while secondary aluminum ash is the product of primary aluminum ash after the extraction of metallic aluminum. It has a relatively lower aluminum content and contains more impurities, making it more difficult to recycle.

[0003] Secondary aluminum ash has been included in the National List of Hazardous Wastes. The nitrides, chlorides, and fluorides in it can form harmful gases such as hydrogen fluoride and ammonia, and may also contain a variety of heavy metals, which pose a serious threat to the soil, groundwater and other environments. On the other hand, secondary aluminum ash still contains considerable aluminum resources, and directly discarding it will also cause a waste of resources.

[0004] With the continuous improvement of green environmental awareness, how to effectively recycle aluminum ash and reduce the consumption rate of mineral resources while removing harmful impurities has become a hot research topic, and many technical solutions have emerged. However, the existing recycling process still has the defects of complex process, low extraction rate and high cost, and the recycled products have poor compatibility and insufficient dispersibility in the actual application of the chemical industry, which affects the quality and performance of the products.

[0005] In summary, it is urgent to develop a new technical solution to overcome the problems existing in the existing technology and meet the development needs of the current market. Summary of the invention

[0006] Based on this, the present invention provides a method for recycling secondary aluminum ash. In the present invention, the secondary aluminum ash is washed with water, mixed with ammonium sulfate and roasted, and then ammonium aluminum sulfate crystals are obtained by water immersion and crystallization, and then high-temperature calcination is performed to obtain aluminum oxide. In order to further improve the functionality of the aluminum oxide material, the present invention uses carboxymethyl cellulose to modify the aluminum oxide, thereby introducing active groups on the surface. While efficiently recycling the secondary aluminum ash, the dispersibility, compatibility and stability of the modified aluminum oxide in the composite material are improved. Using it as a filler in the field of polymer materials can significantly improve product performance.

[0007] An object of the present invention is to provide a method for recycling secondary aluminum ash, the method comprising the following steps:

[0008] S1, pre-treating the secondary aluminum ash by heating and washing, then mixing it with ammonium sulfate, roasting it, and soaking it in water to obtain a leachate, then cooling and crystallizing the leachate, separating the solid, and calcining it to obtain aluminum oxide;

[0009] S2, hydroxylating the aluminum oxide to obtain hydroxylated aluminum oxide;

[0010] S3, blending the hydroxylated alumina and carboxymethyl cellulose, and subjecting them to ultrasonic heating reaction to obtain modified alumina.

[0011] Furthermore, in step S1, the temperature of the heating water washing pretreatment is 80-90°C and the time is 12-36h.

[0012] Furthermore, in step S1, the calcination temperature is 400-500°C and the calcination time is 60-120 minutes.

[0013] Furthermore, in step S1, the water immersion temperature is 50-80°C and the time is 60-120 minutes.

[0014] Furthermore, in step S1, the temperature of the cooling crystallization is 5-15°C, and the time is 2-4h; the temperature of the calcination is 1000-1400°C, and the time is 1-4h.

[0015] Furthermore, in step S2, the hydroxylation treatment is: mixing aluminum oxide and glucose and ball milling them to obtain hydroxylated aluminum oxide.

[0016] Furthermore, in step S3, the temperature of the ultrasonic heating reaction is 50-90° C. and the time is 2-6 hours.

[0017] Furthermore, in step S3, the mass ratio of the hydroxylated aluminum oxide to the carboxymethyl cellulose is 1:(3-10).

[0018] Another object of the present invention is to provide the use of modified alumina prepared by the above-mentioned secondary aluminum ash recycling method in polymer composite materials.

[0019] The beneficial effects of the present invention are:

[0020] In the recycling method and application of secondary aluminum ash of the present invention, the secondary aluminum ash is first washed with water to remove soluble impurities, then mixed with ammonium sulfate, roasted, leached, to generate ammonium aluminum sulfate and extracted into a solution, then stirred at low temperature, cooled and crystallized, to obtain ammonium aluminum sulfate crystals, and then roasted at high temperature to obtain aluminum oxide. In order to improve the dispersibility and compatibility of aluminum oxide as a filler, the present invention further modifies it, firstly ball mills the aluminum oxide to obtain hydroxylated aluminum oxide, then mixes it with carboxymethyl cellulose, and reacts the active hydroxyl groups on the surface of the hydroxylated aluminum oxide with the carboxyl groups of the carboxymethyl cellulose to achieve grafting, thereby introducing cellulose molecules on the surface of the aluminum oxide, so that the surface of the modified aluminum oxide has a large number of carboxyl groups, benzene rings, hydroxyl groups, ester groups and long chains, etc., which not only improves its own dispersibility, but also improves the compatibility with other substances, which is conducive to forming crosslinks or generating intermolecular forces with organic polymer materials, additives and other components in the composite material, thereby exerting a synergistic effect and achieving the improvement of product mechanical properties and stability.

[0021] The invention adopts secondary aluminum ash as raw material and effectively recovers the metal components therein. The process flow is simple and efficient. Green and degradable carboxymethyl cellulose is also used to modify the recovered product, thereby improving various properties of the product. The invention has good application prospects and is of great significance to the further development and promotion of aluminum ash resource utilization. DETAILED DESCRIPTION

[0022] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0023] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0024] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers indicating, for example, the amounts of ingredients used in the specification and claims should be understood to be modified in all cases by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values ​​that vary depending on the desired properties to be obtained by the present invention.

[0025] The secondary aluminum ash in the embodiment of the present invention is taken from the secondary aluminum ash of the local smelter, and the particle size is below 80 meshes.

[0026] The solid-to-liquid ratio in the embodiments of the present invention is expressed in g / mL.

[0027] The carboxymethyl cellulose in the examples of the present invention was purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd. and had an analytical purity.

[0028] Example 1

[0029] A method for recycling secondary aluminum ash comprises the following steps:

[0030] S1. Add secondary aluminum ash to water at a solid-liquid ratio of 1:20, stir at 85°C for 24 hours, filter, wash and dry the solid product, blend with ammonium sulfate (m(solid product): m(ammonium sulfate)=1:7), roast at 450°C for 90 minutes, add to water at a solid-liquid ratio of 1:8 for leaching, the leaching temperature is 70°C, the leaching time is 90 minutes, and then filter to obtain the leachate;

[0031] The leachate is stirred at 10° C. and 300 r / min for 4 hours for cooling and crystallization, solid crystals are separated by filtration, and then ammonium sulfate is added to the filtrate at a solid-liquid ratio of 1:10, and the filtrate volume is evaporated at 70° C. to 65% of the original volume, and then secondary cooling and crystallization are performed, and then the above operation is repeated for three times for cooling and crystallization, and the crystals are collected and dried to obtain ammonium aluminum sulfate;

[0032] The ammonium aluminum sulfate is added into a muffle furnace and calcined at 1200° C. for 2 hours to obtain aluminum oxide with a purity of 98.30%;

[0033] S2, mixing the aluminum oxide and glucose in a mass ratio of 1:5 and ball milling for 12 hours (ball-to-material ratio 5:1), washing, filtering and drying to obtain hydroxylated aluminum oxide;

[0034] S3. Using ethanol as solvent, blend the hydroxylated alumina and carboxymethyl cellulose in a mass ratio of 1:5, perform ultrasonic reaction at 80° C. for 2 h, and obtain modified alumina by filtering, washing and drying.

[0035] Example 2

[0036] A method for recycling secondary aluminum ash comprises the following steps:

[0037] S1. Add secondary aluminum ash to water at a solid-liquid ratio of 1:20, stir at 80°C for 36 hours, filter, wash and dry the solid product, blend with ammonium sulfate (m(solid product): m(ammonium sulfate)=1:6), roast at 430°C for 90 minutes, add to water at a solid-liquid ratio of 1:8 for leaching, the leaching temperature is 65°C, the leaching time is 90 minutes, and then filter to obtain the leachate;

[0038] The leachate is stirred at 10° C. and 300 r / min for 4 hours for cooling and crystallization, solid crystals are separated by filtration, and then ammonium sulfate is added to the filtrate at a solid-liquid ratio of 1:10, and the filtrate volume is evaporated at 70° C. to 65% of the original volume, and then secondary cooling and crystallization are performed, and then the above operation is repeated for three times for cooling and crystallization, and the crystals are collected and dried to obtain ammonium aluminum sulfate;

[0039] The ammonium aluminum sulfate is added into a muffle furnace and calcined at 1200° C. for 3 hours to obtain aluminum oxide with a purity of 98.28%;

[0040] S2, mixing the aluminum oxide and glucose in a mass ratio of 1:5 and ball milling for 12 hours (ball-to-material ratio 5:1), washing, filtering and drying to obtain hydroxylated aluminum oxide;

[0041] S3. Using ethanol as solvent, blend the hydroxylated alumina and carboxymethyl cellulose in a mass ratio of 1:6, perform ultrasonic reaction at 80° C. for 3 h, and obtain modified alumina by filtering, washing and drying.

[0042] Example 3

[0043] A method for recycling secondary aluminum ash comprises the following steps:

[0044] S1. Add secondary aluminum ash to water at a solid-liquid ratio of 1:20, stir at 85°C for 28 hours, filter, wash and dry the solid product, blend with ammonium sulfate (m(solid product): m(ammonium sulfate)=1:6), roast at 425°C for 90 minutes, add to water at a solid-liquid ratio of 1:8 for leaching, the leaching temperature is 60°C, the leaching time is 90 minutes, and then filter to obtain the leachate;

[0045] The leachate is stirred at 10° C. and 300 r / min for 4 hours for cooling and crystallization, solid crystals are separated by filtration, and then ammonium sulfate is added to the filtrate at a solid-liquid ratio of 1:10, and the filtrate volume is evaporated at 70° C. to 65% of the original volume, and then secondary cooling and crystallization are performed, and then the above operation is repeated for three times for cooling and crystallization, and the crystals are collected and dried to obtain ammonium aluminum sulfate;

[0046] The ammonium aluminum sulfate is added into a muffle furnace and calcined at 1200° C. for 2 hours to obtain aluminum oxide with a purity of 98.34%;

[0047] S2, mixing the aluminum oxide and glucose in a mass ratio of 1:5 and ball milling for 12 hours (ball-to-material ratio 5:1), washing, filtering and drying to obtain hydroxylated aluminum oxide;

[0048] S3. Using ethanol as solvent, blend the hydroxylated alumina and carboxymethyl cellulose in a mass ratio of 1:6, perform ultrasonic reaction at 80° C. for 3 h, and obtain modified alumina by filtering, washing and drying.

[0049] Comparative Example 1

[0050] A method for recycling secondary aluminum ash. The difference between this comparative example and Example 1 is that steps S2-S3 are omitted and the aluminum oxide prepared in step S1 is used as the product.

[0051] Comparative Example 2

[0052] A method for recycling secondary aluminum ash. The difference between this comparative example and Example 1 is that in step S3, an equal mass of lauric acid is used to replace carboxymethyl cellulose to obtain lauric acid-modified alumina.

[0053] Application Examples

[0054] The modified alumina prepared in the examples and comparative examples is used as a filler in a polymer material, wherein the polymer material comprises the following components in parts by mass:

[0055]

[0056]

[0057] The preparation method of the polymer material comprises the following steps:

[0058] According to the above-mentioned mass fractions, polypropylene resin (SK Chemical BX3800, South Korea), polystyrene resin (Shanghai Secco GPPS 251P), POE resin (Exxon 5061), filler (modified alumina prepared by Examples 1-3 and Comparative Examples 1-2, respectively), antioxidant 1010, melamine and sodium dodecyl sulfate were uniformly mixed, added into a twin-screw extruder and extruded and granulated at 190° C. to obtain polymer materials 1-5.

[0059] Test Case

[0060] The polymer materials 1-5 prepared according to the corresponding examples were subjected to performance tests.

[0061] Test method: Tensile strength, flexural strength and other performance tests are carried out in accordance with ISO 178, ISO 180 and ISO 527-2 standards.

[0062] The test results are shown in Table 1.

[0063] Table 1 Performance test results

[0064] project Tensile strength / MPa Bending strength / MPa <![CDATA[Notched impact strength / KJ / m 2 > Polymer Materials 1 56.9 93.9 10.7 Polymer Materials 2 57.4 94.8 10.8 Polymer Materials 3 57.8 95.4 10.8 Polymer Materials 4 40.2 77.6 8.6 Polymer Materials 5 49.6 87.4 9.9

[0065] According to Table 1, it can be seen that the mechanical properties of polymer materials 1-3 prepared by modified alumina of Examples 1-3 are significantly better than those of polymer materials 4-5 prepared by Comparative Examples 1-2. Comparative Examples 1-2 do not perform surface modification on alumina, or use fatty acid segments for modification, resulting in unsatisfactory improvement in dispersibility and compatibility of inorganic fillers, and cannot be compounded with other components to obtain good synergistic effects, resulting in poor comprehensive performance. In summary, the present invention solves the defects of the prior art and is conducive to the further development and application of aluminum ash resources.

[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0067] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for recycling secondary aluminum ash, characterized in that: The secondary aluminum ash recycling method comprises the following steps: S1, pre-treating the secondary aluminum ash by heating and washing, then mixing it with ammonium sulfate, roasting it, and soaking it in water to obtain a leachate, then cooling and crystallizing the leachate, separating the solid, and calcining it to obtain aluminum oxide; S2, hydroxylating the aluminum oxide to obtain hydroxylated aluminum oxide; S3, blending the hydroxylated alumina and carboxymethyl cellulose, and subjecting the mixture to ultrasonic heating reaction to obtain modified alumina; In step S3, the mass ratio of the hydroxylated aluminum oxide to the carboxymethyl cellulose is 1:(3-10); In step S1, the temperature of the heating water washing pretreatment is 80-90°C and the time is 12-36 hours; In step S1, the calcination temperature is 400-500°C and the calcination time is 60-120 min; In step S1, the water immersion temperature is 50-80°C and the time is 60-120 min; The modified alumina prepared by the secondary aluminum ash recycling method is used in a polymer composite material, wherein the polymer composite material comprises polypropylene resin, polystyrene resin, POE resin and modified alumina.

2. The method for recycling secondary aluminum ash according to claim 1, characterized in that: In step S1, the temperature of the cooling crystallization is 5-15°C and the time is 2-4 h; the temperature of the calcination is 1000-1400°C and the time is 1-4 h.

3. The method for recycling secondary aluminum ash according to claim 1, characterized in that: In step S2, the hydroxylation treatment is: mixing aluminum oxide and glucose and ball milling them to obtain hydroxylated aluminum oxide.

4. The method for recycling secondary aluminum ash according to claim 1, characterized in that: In step S3, the temperature of the ultrasonic heating reaction is 50-90° C. and the time is 2-6 h.

Citation Information

Patent Citations

  • Method for preparing aluminum oxide from aluminiferous material

    CN101734698A

  • Method for extracting aluminum from secondary aluminum ash and application of aluminum-containing solution

    CN106834739A

  • Heat-conducting plastic master batch, preparation method thereof and heat-conducting plastic

    CN110172166A

Cited By

  • Continuous preparation method of high-quality premelting type calcium aluminate based on secondary aluminum ash

    CN120887443A

  • Heat-conducting filler, organic silicon heat-conducting pouring sealant, and preparation method and application of heat-conducting filler and organic silicon heat-conducting pouring sealant

    CN122167825A